Elenchos : Journal of Studies on Ancient Thought (De Gruyter, 2017)
Elenchos covers all aspects of the study of ancient Greek and Roman Thought from an historical as well as from a thematic point of view, aiming to serve as a venue for different approaches and methodologies in Ancient Philosophy. Each issue consists of four parts: articles and essays; discussions; reviews; and short notes.